Profile of champions in health promotion in a community setting : an exploratory study - Osseiran-Moisson, Rebecca (Curtin University, 2011)
Chronic diseases such as cardiovascular diseases and diabetes can be prevented by acting on risk factors such as tobacco use, an unhealthy diet and lack of exercise. As behaviour is influenced at multiple levels, individual and environmental, the most effective intervention needs to explore these multiple levels.The background of this study is a novel and successful approach: “the Waist Disposal Challenge” (WDC) which induced lifestyle behavioural changes. The WDC was a pilot health intervention designed to reduce weight and other risk factors for chronic diseases. The WDC was implemented during 2007-2008 in 23 Rotary clubs in the South West of Western Australia. Findings showed a significant to moderate weight loss amongst participants and other lifestyle changes. It is believed the natural helpers (called Champions), who promoted and facilitated the program in clubs, played a pivotal role in this program.The purpose of this study was to examine the role, attitudes, motivating factors and common characteristics of these Champions (also referred to as lay health advisors in the literature) or in other terms to define the appropriate profile for such lay leaders in community based health promotion programs. As the focus in delivering health interventions is to rely more on peer educators or lay leaders to spread healthy messages and change peer behaviours, the attributes of who is appropriate for this role is important for the success of health programs that are led by the community.An exploratory descriptive design using a mixed method approach was adopted for this study. From a purposive sample of 27 Champions, 20 completed a developed self-administered survey. Semi-structured interviews with Champions were then conducted to gather more in-depth data about their experience in this role. From a purposive sample of 40 Club Members who participated in all stages of the WDC, 21 completed a survey reflecting on their experience of this program and on their perception on how the role played by the Champion affected their decision to participate and/or change certain behaviours.Results indicated that most of the Champions had a leadership position on the Executive board of their own clubs. The main motivating factors to hold a Champion position were their interest in health, in the WDC program to help their peers and for some it was for personal need to lose weight. Generally Champions expressed confidence and enthusiasm and found new strategies to sustain the WDC. The support of club hierarchy and club members played an important part in the role of the Champions. Findings brought to light the crucial importance of the impact of the organisational interaction within the Rotary club on the Champion‟s role, which could not be defined without taking into account club members‟ synergy, club hierarchy, sense of community and knowledge of club‟s norms.Findings revealed that all Club Members were male and most of them lost weight during the WDC. Less than half of the Club Members thought that their Champion played a crucial role in their decision to participate in the WDC. Almost half of the Club Members found that their Champions were a role model who they could identify with. Like the Champions, Club Members had a high sense of community.The comparative analysis, which was speculative due to the small sample size, demonstrated that there could be important differences between Champions whose clubs lost weight and Champions whose clubs did not lose weight that had influenced the success of the WDC.The results highlighted the pivotal role of these Champions in promoting and sustaining a health promotion program in community settings. However limitations due to the cross-sectional nature, purposive sample and sample size of the study meant that the results could not be generalized beyond the studied population and results from this explorative research needed to be interpreted with caution. Further research is needed with a larger sample size to determine the extent of the influence these champions had on the success of the implementation and sustainability of the health intervention.